Considerations for spectroscopy of liquid-exfoliated 2D materials: emerging photoluminescence of N-methyl-2-pyrrolidone. Issue 1 (December 2017) - Ogilvie, Sean; Large, Matthew; Fratta, Giuseppe; Meloni, Manuela; Canton-Vitoria, Ruben; Tagmatarchis, Nikos; Massuyeau, Florian; Ewels, Christopher; King, Alice; Dalton, Alan
Abstract N -methyl-2-pyrrolidone (NMP) has been shown to be the most effective solvent for liquid phase exfoliation and dispersion of a range of 2D materials including graphene, molybdenum disulphide (MoS2 ) and black phosphorus. However, NMP is also known to be susceptible to sonochemical degradation during exfoliation. We report that this degradation gives rise to strong visible photoluminescence of NMP. Sonochemical modification is shown to influence exfoliation of layered materials in NMP and the optical absorbance of the solvent in the dispersion. The emerging optical properties of the degraded solvent present challenges for spectroscopy of nanomaterial dispersions; most notably the possibility of observing solvent photoluminescence in the spectra of 2D materials such as MoS2, highlighting the need for stable solvents and exfoliation processes to minimise the influence of solvent degradation on the properties of liquid-exfoliated 2D materials.